Choice of Fresh Vegetable Retail Outlets by Developing-Country Urban Consumers: The Case of Kale Consumers in Nairobi, Kenya - Okello, Julius J.; Lagerkvist, Carl-Johan; Hess, Sebastian; Ngigi, Marther; Karanja, Nancy (My University, 2012)
Fresh produce retailing in many developing-country urban centers is changing with the recent emergence and rapid growth of supermarkets and specialty stores. These retail outlets are competing with the traditional wet markets in developing-country urban centers for buyers. This article uses information obtained from interviews with 449 kale consumers in Nairobi to assess the factors conditioning their choice between open-air markets, roadside markets, supermarkets and specialty markets when buying fresh vegetables. It uses non-parametric methods to identify these factors and then tests the causal effect of the identified factors on choice of retail outlet by consumers using parametric techniques. Both the non-parametric and parametric methods identify income, level of education, risk perception, living environment, level of willingness to pay for safe kale, and confidence in the consistency of quality of kale as the major conditioners of the choice of retail outlet by consumers. The article discusses the implications of these findings. La distribution de produits frais est en pleine e´volution dans de nombreux pays en de´veloppement, avec l’apparition re´cente et le de´veloppement rapide des grandes surfaces et magasins spe´cialise´s. Ces distributeurs rivalisent avec les marche´s ouverts traditionnels dans les centres urbains des pays en de´veloppement. Cette e´tude mobilise des donne´es issues d’entretiens re´alise´s a` Nairobi avec 449 consommateurs de chou frise´, dans le but de de´terminer les facteurs qui les influencent dans leur choix d’acheter leurs le´gumes frais dans des marche´s a` ciel ouvert, de bord de route ou dans des grandes surfaces et magasins spe´cialise´s. Elle s’appuie sur des me´thodes non-parame´triques pour identifier ces facteurs, et mobilise ensuite des techniques parame´triques pour tester l’effet causal des facteurs repe´re´s sur le choix de distributeurs par les consommateurs. Les me´thodes non parame´triques et parame´triques permettent d’identifier les revenus, le niveau d’e´ducation, la perception du risque, le cadre de vie, la disposition a` payer pour du chou sain et la confiance dans sa qualite´ comme facteurs importants du choix de tel ou tel type de distributeurs par les consommateurs. L’article analyse les implications de ces re´sultats.
Keywords: Fresh vegetables; Urban consumers; Market choice; Developing countries; Kenya